ANALYSIS OF THE IMPACT OF RISK MANAGEMENT STRATEGIES ON THE FINANCIAL PERFORMANCE OF BUDI KARYA MAJU COMPANY - Budiyono Budiyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the impact of risk management strategies on the financial performance of Budi Karya Maju Company. The research method used is in the form of a case study at Budi Karya Maju's company. Researchers conduct analysis on the company's annual financial statements which include balance sheets, income statements, and cash flow statements, besides that researchers also collect information related to the implementation of risk management strategies carried out by the company in the same period. The result of this study is that during 2022, Budi Karya Maju implemented a risk management strategy that focuses on mitigating operational risks and financial risks so that the risk management strategy implemented by Budi Karya Maju has a real positive impact on the company's financial performance, increasing net profit, revenue, and overall financial stability